1999
DOI: 10.1046/j.1460-9568.1999.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered synaptic clustering of GABAA receptors in mice lacking dystrophin (mdx mice)

Abstract: Dystrophin is selectively localized in the postsynaptic density of neurons in cerebral cortex, hippocampus and cerebellum. Here, we show by double-immunofluorescence staining that dystrophin is extensively colocalized with GABAA receptor subunit clusters in these brain regions. To determine the relevance of this observation, we investigated in mdx mice, which provide a model of Duchenne muscular dystrophy, whether the absence of dystrophin affects the synaptic clustering of GABAA receptors. A marked reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
203
2
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 219 publications
(241 citation statements)
references
References 16 publications
(40 reference statements)
30
203
2
3
Order By: Relevance
“…The cognitive impairments lead to speculation that the dystrophin protein family may play a key role at neuronal synapses. Best evidence for such a role comes from reports that full-length dystrophin regulates the stability of selective GABA A receptors and α3-containing nAChRs at a subset of central GABAergic and peripheral sympathetic nicotinic synapses (Knuesel et al, 1999(Knuesel et al, , 2001Zaccaria et al, 2000;Del Signore et al, 2002;Levi et al, 2002;Fritschy et al, 2003). However, our findings do not support a postsynaptic role for dystrophin and utrophin proteins at nicotinic synapses in parasympathetic CG neurons.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…The cognitive impairments lead to speculation that the dystrophin protein family may play a key role at neuronal synapses. Best evidence for such a role comes from reports that full-length dystrophin regulates the stability of selective GABA A receptors and α3-containing nAChRs at a subset of central GABAergic and peripheral sympathetic nicotinic synapses (Knuesel et al, 1999(Knuesel et al, , 2001Zaccaria et al, 2000;Del Signore et al, 2002;Levi et al, 2002;Fritschy et al, 2003). However, our findings do not support a postsynaptic role for dystrophin and utrophin proteins at nicotinic synapses in parasympathetic CG neurons.…”
Section: Discussioncontrasting
confidence: 77%
“…Dystrophin also localizes to a subset of α3-nAChR-rich postsynaptic sites in sympathetic superior cervical ganglion (SCG) neurons Zaccaria et al, 2000;Del Signore et al, 2002). Although dystrophin is not required for cluster formation, there are decreases in the number of GABA A receptor and α3-containing nAChR clusters and impaired inhibitory synaptic transmission inmdx and dystrobrevin mutant mice Knuesel et al, 1999;Zaccaria et al, 2000;Del Signore et al, 2002;Anderson et al, 2003;Grady et al, 2006;Kueh et al, 2008). These studies define a specific neural function for dystrophin and its associated glycoprotein complex.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In neurons, dystrophin was shown initially to be present in PSD fraction of purified brain membranes [86]. Subsequent studies demonstrated its association with a subset of GABAergic synapses [87,88], where it regulates GABA A R clustering and GABAergic synaptic function, as well as glutamatergic synaptic plasticity (reviewed in [83,82]). In mdx mice, direct involvement of dystrophin in synaptic alterations has been demonstrated by dystrophin rescue experiments, which normalize mIPSC amplitude and frequency, as well as LTP in CA1 pyramidal cells [89,90].…”
Section: The Dystrophin-glycoprotein Complexmentioning
confidence: 99%
“…For example, treatment of the rat hippocampus with NRG1 resulted in lower expression of GABA A receptor subunit transcripts, 66 while dysbindin likely colocalizes with GABA A receptor subunits in the hippocampus, cortex, and cerebellum through its association with beta-dystrobrevin in the dystrophin protein complex. [67][68][69] Despite the evidence for GABA system alterations in schizophrenia patients, there has been little investigation of association between GABA receptor genes and schizophrenia, although association with the GABRB2 gene was recently reported in a Chinese patient sample. 70 We performed an association study of the 5q GABA A receptor subunit gene cluster in schizophrenia based on: (1) strong meta-analytic evidence for linkage between schizophrenia and chromosome 5q, (2) linkage to 5q in our Portuguese schizophrenia families, (3) evidence for involvement of the GABA system in schizophrenia, and (4) location of the GABA A receptor subunit gene cluster in the 5q risk locus.…”
Section: Introductionmentioning
confidence: 99%